PELATIHAN MANAJEMEN DIRI UNTUK PENGEMBANGAN KETERAMPILAN DI RUMAH YATIM DAN DHUAFA AL-AMIEN CIATER, TANGERANG SELATAN - Supatmin, Supatmin; Maulana, San Ridwan; Indirasari, Indirasari (Yayasan Education and Social Center, 2024)
This Community Partnership Program (PKM) aims to develop self-management skills for orphans and underprivileged children at Al-Amien Orphanage and Dhuafa House in Ciater, South Tangerang. The program implementation method includes 3 days of training covering self-awareness, time management, effective communication, and basic skills such as sewing, cooking, and gardening. The training results show improvements in aspects of self-understanding and self-confidence, time management abilities, communication skills, and mastery of basic skills. This program has successfully made a positive impact on participants' personal development and skills, and can serve as a model for similar program development elsewhere.